Activity of Ceftolozane-Tazobactam Against Global Pseudomonas Aeruginosa and Non-Susceptible Phenotypes: SMART 2016. (4th October 2017) - Lob, Sibylle; Hackel, Meredith; Badal, Robert; Young, Katherine; Motyl, Mary; Sahm, Dan
Abstract: Background: Pseudomonas aeruginosa (PA), one of the species of the ESKAPE pathogens that are known to "escape" the effects of many antimicrobials, is often difficult to treat. Ceftolozane-tazobactam (C/T) is an anti-pseudomonal cephalosporin/β-lactamase inhibitor recently approved by FDA and EMEA. We examined its activity against global clinical isolates of PA, including isolates non-susceptible (NS, intermediate or resistant) to other agents. Methods: In 2016, 158 hospitals in 51 countries collected 5533 PA from intra-abdominal (IAI), urinary (UTI), and respiratory tract infections (RTI). MICs were determined using CLSI broth microdilution and interpreted with both CLSI and EUCAST breakpoints, as the susceptible breakpoints for C/T, cefepime (FEP), meropenem (MEM), and piperacillin-tazobactam (P/T) are the same using both criteria. Results: Overall regional susceptibility of PA to C/T, prevalence of FEP-NS, MEM- NS, and P/T- NS phenotypes, and susceptibility of these phenotypes to C/T are shown below: Conclusion: Overall susceptibility to C/T ranged from 85% in Latin America to 98% in South Pacific. FEP-NS, MEM-NS, and P/T-NS isolates were least prevalent in South Pacific. C/T was active against these phenotypes in >80% of isolates in North America and South Pacific and against 62–73% of MEM-NS and P/T-NS isolates in all other regions except Latin America. Monitoring of C/T susceptibility to PA is warranted in light of increasing resistance to first line agents. Disclosures: M. Hackel, IHMA: Employee,  Salary; R. Badal, IHMA, Inc: Employee,  Salary; K. Young, Merck: Employee and Shareholder, Dividends and Salary M. Motyl, Merck & Co., Inc., : Employee, Salary